Women's formal networking: The relationship between networking activities and power. Issue 5 (21st May 2022) - Papafilippou, Vanda; Durbin, Susan; Conley, Hazel
Abstract: This article examines the networking that takes place within formally organized internal (organization‐based) and external (industry‐based) women engineers' networks. Drawing upon 48 interviews with women engineers, across a number of industries and seniority levels, mostly in the UK, the article contributes to the scarce empirical literature examining formal women's networking in engineering, in terms of its role in individual support and collective change. By adopting Allen's (1998, 1999) definition of feminist power and shifting the focus of analysis from merely instrumental to other types of networking activities, the study contributes empirically and theoretically to understanding how internal and external women's networking has the potential to help female engineers to stay in and change the profession. Despite the critiques that formal women's networks lack power and the ability to make a positive difference for women, when feminist conceptualizations of power are adopted, women's networking within these networks can be considered to empower them in a variety of ways. Our data identifies that wider networking within external women's networks can be particularly useful as a force for change.